Uma proposta de avaliação do efeito da Lei Complementar 194/2022 sobre a arrecadação do ICMS no Estado do Ceará, Nordeste e Brasil - Prado Júnior, Jackson Emanuel Benevides (2024)
The study proposes an assessment of the impacts of Complementary Law 194/2022 on ICMS collection in the energy and fuel segments at three levels: for the State of Ceará, for the Northeast Region and for Brazil. Representativeness indicators for the ICMS collected in these segments were calculated at the three respective levels and the results suggested a structural change in the collection pattern after the implementation of this device that changed the ICMS rates in the two segments analyzed. Unit root tests with structural break were applied to the proposed indicators and it was found that: i) LC 194/2022 represented a structural change in the state, Northeast Region and national ICMS collection pattern and; ii) in the State of Ceará and the Northeast Region for the energy segment and in Brazil, for the fuel segment, there is a divergent dynamic between the ICMS collection in these segments and the total collection, suggesting that the rate reduction was not compensated by the increase in consumption, so as to see a continued drop in revenue from the aforementioned tax.